RISK FACTORS FOR GALL BLADDER CANCER IN KARACHI - Rizvi, Talat J. H.; Zuberi, Sarwar J. (Journal of Ayub Medical College Abbottabad, 2003)
Background: Frequency of gallbladder cancer in Karachi has been reported to be 8% and that from other parts of Pakistan varies between 6-7%. This is very high as compared with the Western studies. With this in mind a case control study was designed to identity risk factors responsible for gallbladder cancer. Methods: This case control study included 107 histologically proven cases of gall bladder cancer from Jinnah Postgraduate Medical Centre, Civil Hospital and two private hospitals of Karachi. Age and sex matched controls were of two types. Those with and without cholelithiasis screened sonographically. Demographic, socio-economic factors, life-style, dietary habits and dietary intake were recorded on a proforma. The cases and controls were compared for various factors using odds Ratio. Results: Among 107 cancer cases 27 were males and 80 females (M:F=1:3). Mean age of males was 59 years (range 35-82 years) and females 53years (range 31-70 years). One hundred and five (98%) had associated choleliathiasis. Important risk factors appeared to be gallstones, high parity, young age at first delivery, low fiber and Vitamin A intake (p<0.01), high fat intake (p<0.01), prolonged fasting hours/habit of missing dinner(OR:6.8), using repeatedly boiled or improperly stored ghee or oil(OR:2.6). Conclusions: According to this case-control study major risk factors for gall bladder cancer were gallstones, dietary mal practices and poorly balanced diet. Poorly stored/ processed food acts as a promoter in the presence of gall stones and may favour cancer development. Key words: Gallbladder carcinoma, choleliathiasis, diet, dietary habits.